Sonata for piano n. 1 by Francisco Mignone: a performance comparison (Orfeu, 2018)
This paper investigates some of the interpretive decisions related to the timing, dynamics and articulation of four renditions of the first movement of Piano Sonata n.1 by Francisco Mignone. Through the comparison of recordings expressive strategies adopted by performers widely recognized for their level of expertise have been identified. In the process of comparison it has become evident how the expressive direction of the musical discourse as well as the different sections of the piece result from the coordinated manipulations of timing and dynamics.
Keywords: Sonata n. 1 for piano by Francisco Mignone; expressivity profiling; timing and dynamic; rhythmic analysis; analyses of recordings